Evaluación del producto de precipitación PISCO y ERA5 para generar Caudales Diarios en la cuenca del río Pativilca - Sarango, Douglas (2025)
The gridded daily precipitation data from PISCO v2.1 and ERA5 are evaluated by applying the GR4J hydrological model to generate daily flows in the sub-basins located upstream of the Cahua hydrometric station, in the upper Pativilca River basin, under a semi-distributed approach by sub-basins. The RS Minerve platform is used for the construction of the semi-distributed hydrological model. 33 sub-basins upstream of the Cahua hydrometric station were identified using QGIS software. The gridded precipitation data from PISCO v2.1 and ERA5 were validated based on 14 rain gauge stations located in the study basin and nearby areas, with historical precipitation records that were statistically analyzed to assess their reliability. When applying the semi-distributed sub-basin GR4J hydrological model, in the calibration stage (2000-2010), a Nash-Sutcliffe value of 0.76 was obtained using the daily precipitation information PISCO v2.1 and a value of 0.74 when using the daily precipitation information from ERA5. In the model validation stage (2011-2016), Nash-Sutcliffe values ​​of 0.79 and 0.75 were obtained using the daily precipitation information from the aforementioned databases. The results obtained indicate that with the daily information from PISCO v2.1, the semi-distributed sub-basin GR4J hydrological model better represents the daily natural flows occurring in the Pativilca basin.